A Study of the Role of Hemolysis in the Hemostatic Defect of Transfusion Reactions - Langdell, R. D; Hedgpeth, E. M, Jr. (Thrombosis and Haemostasis, 1959)
Hemoglpbinemia of approximately 300 mg% was produced in dogs by five separate methods. Resulting from the infusions of incompatible plasma or erythrocytes there was a hemostatic defect characterized by severe thrombocytopenia and moderate fibrinogenopenia. Associated with this were leukopenia, neuromuscular and cardio-respiratory disturbances. Except for hemoglobinemia resulting from infusion of autologous hemoglobin solution, distilled water, or glucose-damaged autologous erythrocytes, no systemic reaction was detected. These findings indicate that the liberation of thromboplastic erythrocyte components by hemolysis is not the mechanism of the hemostatic defect in hemolytic transfusion reactions.Acknowledgment. Canine anti-A serum was obtained through the courtesy of Lt. Col. J. H. Akeroyd, Walter Reed Army Institute of Research, Washington, D. C.